GENDER DISPARITY IN AGRICULTURAL CREDIT FACILITIES AND INPUT DISTRIBUTION IN BOGORO LOCAL GOVERNMENT AREA, BAUCHI STATE - Abdullahi, I. M.; Jatbong, J. N.; Baraza, S. A.; Sylvanus, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examines gender disparity in agricultural credit facilities and input distribution in Bogoro Local Government Area. Data were collected and analyzed using simple descriptive statistics and the regression analysis. Findings revealed that 96% of the farmers were aged between 25 to 50 years while 80% were male. The results further showed that 70% were married, 22% were single with an average farming experience of 10years. In addition, the results revealed that majority (60%) of the respondents disagreed that women had equal access to credit facilities to their men counterparts while 50% agreed that women were informed about the credit facilities in comparison to men. Also, majority (70%) of the respondents disagreed that there was fairness in credit approval to women in comparison to their men counterparts. The results of regression analysis revealed that age (0.05), educational qualification (0.05), farming experience (0.01) were the significant factors influencing farmers’ access to agricultural credit. The results also revealed that the major constraints include; lack of collateral, discriminatory practices and limited financial literacy. In conclusion, there exist a gender disparity in women access to credit facilities and fairness of approval compared to their men counterparts in the study area. The study therefore recommends that government should advance adequate farm credit to farmers irrespective of gender to enable them improve food production as well as ensure food security in the area. A supervised credit scheme should be set up by the government as well as functional and effective credit access which would serve as panacea for gender differential in credit access.